METODOLOGI KLASIFIKASI QATHIY DAN ZHANNIY MENURUT IMAM ASY-SYATHIBI - Sugeng Wanto (Ibn Abbas : Jurnal Ilmu Alquran dan Tafsir, 2019)
The categorization of the verses of the Koran to the qath’iy and zhanniy, actually does not exist either in the Koran, the sunnah of the opinions of friends, tabi'in or the Imam of the great school of thought. Thus, this categorization is the creation of recent scholars who are seen as a product of ijtihad. Because the categorization is a product of ijtihad, in fact, the notion of qathiy and zhanniy should not be viewed dogmatically. Because as a product of ijtihad it continues to apply relativity, not absolute. Imam as-Syatibi has a different concept from the popular opinion about qath'iy and zhanniy, from his statement it seems that there is no qathiy in the texts of syara ’or even if it is very rare. According to him, keqathiyan was drawn and deduced from a number of texts both the Koran and the traditions that have the same meaning or mutual support so that the meanings contained in the various texts converge fully and cohesively on a particular idea or concept. Keywords: Qath'iy, Zhanniy.